Impact of PM10 Exposure and Socio-Demographic Aspect With Lung Function Disorders - Siti Rachmawati; Iwan Suryadi; Juherah Juherah; Abdur Rivai; Nurlaila Fitriani; Fathoni Firmansyah; Rina Zam Ratun (Jurnal Kesehatan Masyarakat, 2023)
The concentration of PM2․5 and PM10 particles is a major problem and the primary environmental health risk that causes premature death. This study aims to examine the effect of PM10 exposure and socio-demographic aspects on lung function disorders of bus Terminal workers exposed to traffic emissions. This research used a cross-sectional approach. The population is 96 people, and 50 became samples according to the purposive sampling criteria. The measurement of lung vital capacity is by spirometry. The high-volume air sampler was applied to measure dust concentration, and the questionnaire was used to assess individual characteristics. The independent variables of this research are PM10 concentration, age, smoking behavior, working period, type of work, education, use of masks, and body weight. The dependent variable is impaired lung function. The bivariate analysis showed that exposure to PM10, smoking behavior, years of service, and use of masks were significant for impaired lung function. The result of multivariate analysis of dust is the most relevant to the lung vital capacity. In conclusion, dust concentrations are classified above the Threshold Limit Value (TLV), so government should control the source of dust exposure.